SISTEM PENGONTROLAN INTENSITAS CAHAYA PADA PERANGKAT SMART GREENHOUSE UNTUK TANAMAN HIAS PURING MENGGUNAKAN FUZZY LOGIC CONTROL DENGAN METODE MAMDANI - Muhammad Akbar Kamal; Muhammad Aziz Muslim; Goegoes Dwi Nusantoro (Jurnal Mahasiswa TEUB, 2023)
During the Covid-19 pandemic, the cultivation of ornamental plants became one of the activities that people liked a lot. That's because ornamental plants have a value of beauty and attractiveness, so they are usually used for decoration. However, the ways to care for ornamental plants are very diverse and have varying difficulties. The croton plant (Codiaeum Variegatum) is an ornamental plant that stands out on the leaves, the croton plant grows in 2 tropical climates and really needs sunlight. The benefits of the croton plant apart from being an ornamental plant, can also degrade the pollutants around it. With the aim of optimizing the cultivation of croton plants, a device is needed that is able to properly meet all the needs of croton plants. Testing begins with designing the control system and device design. Then proceed with making a prototype device and testing according to the characteristics of croton plants. Furthermore, data collection and data analysis were carried out using fuzzy logic control with the mamdani method. The fuzzy logic control will adjust the light intensity produced by the LED grow light. The setpoint in the test is 600 lux which is the ideal lighting for croton plants. The test results show that the LDR sensor used has an error of 0.08% with a reading error tolerance of ±2%. The sensor readings on each side of the smart greenhouse device can be said to be the same. The condition of the actuator in the power range of 70%-100% is bright, 50%-60% is dim and 0%-40% is off. The results of LED grow light lighting are in accordance with the setpoint. However, the system response can be said to be quite slow to reach the setpoint. The effect of implementing croton ornamental plants on a smart greenhouse device which was carried out for 14 days (2 weeks) resulted in a change in the initial plant height of 21.8 cm to 25.3 cm with a total growth of 3.5 cm and a more striking change in leaf color (redness) and therefore the device can function according to the design that has been made. Keywords: Light Intensity, Smart Greenhouse, Fuzzy Logic Control, Fuzzy Mamdani